BATCH SCHEDULING MODEL FOR HYBRID FLOWSHOP WITH ASSEMBLY AND DEDICATED MACHINES TO MINIMIZE TOTAL ACTUAL FLOW TIME - SHOLIKHA, NIKMATUS
This research concerns a batch scheduling problem for hybrid flowshop with assembly and dedicated machines which consists of five stage. The first stage is fabrication, this stage consists of several groups of parallel machines where each group of machines produces different component. The second stage is the machining process using dedicated machines. The third and fourth stages are sub-assembly operations and assembly operation respectively. The fifth stage is differentiation stage to produce different types of products efficiently. Backward approach is used to perform scheduling. The decision variables in this research are the number of batch, the batch size, and the batch processing sequence. The objective of this research is to minimize total actual flow time. In this research, all the completed parts should be delivered at a common due date. The solution starts by determining the number of batch and the batch size, then scheduling. Solutions of the model is obtained by applying software LINGO 11.0 and an algorithm proposed for practical condition. Numerical experiments show that the proposed model can solve the problem with optimal solutions. The proposed model is sensitive to demand, types of items, and number of machines, but it is not sensitive in the due date parameters.